Electrically detachable single-component siloxane modified heat-conducting polyurethane hot melt adhesive as well as preparation method and application thereof

By introducing the introduction of silicoline modified polyurethane prefabricated and modified filler compositions in the thermal polyurethane thermal melting glue, combined with electrolyte salt and silicane coupling agent, the existing thermal polyurethane thermal melt glue is in bonding strength and thermal conductivity. The deficiencies have realized high -performance adhesives that are dismantled and dismantled, and are suitable for heat dissipation adhesion applications of electronic equipment.

CN119351033AActive Publication Date: 2025-01-24XIAMEN WELDTONE TECH CO LTD

Patent Information

Application Number
CN202411460625.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing thermally conductive polyurethane hot melt adhesives have shortcomings in their bonding strength and thermal conductivity, and are difficult to achieve rapid disassembly, affecting the heat dissipation performance and safety of electronic equipment.

Method used

One-component silicone modified thermally conductive polyurethane hot melt adhesive is used. By introducing silicone modified polyurethane prepolymer and modified filler composition into the adhesive, combined with electrolyte salt and silane coupling agent, the thermal conductivity is improved. and bonding strength, and achieves disassembly function under energized conditions.

Benefits of technology

A adhesives that have good thermal conductivity, excellent adhesion performance, and dismantling and disassembly can be used. It is suitable for the heat dissipation adhesive application of high -performance electronic equipment, which improves the safety and reliability of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091766130000191
    Figure BDA0005091766130000191
Patent Text Reader

Abstract

The invention belongs to a polyurethane hot melt adhesive, and relates to an electrically detachable single-component siloxane modified heat-conducting polyurethane hot melt adhesive as well as a preparation method and application thereof. The electrically detachable single-component siloxane modified heat-conducting polyurethane hot melt adhesive contains a siloxane modified polyurethane prepolymer, a modified filler composition, an optional catalyst and an optional water absorbent, wherein the modified filler composition contains heat-conducting filler, electrolyte salt, a silane coupling agent and an optional polar solvent compound; after the electrically detachable single-component siloxane modified heat-conducting polyurethane hot melt adhesive is electrified under the voltage of 1-100 V, the bonding strength is attenuated by 80% or above. The single-component silane modified heat-conducting polyurethane hot melt adhesive provided by the invention has the advantages of being good in heat-conducting property, excellent in adhesive property and detachable after being electrified, and has a wide practical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to polyurethane hot melt adhesive, and relates to an electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive, and a preparation method and application thereof. Background Art

[0002] With the continuous development and maturity of the electronics industry, the size of internal devices of electronic devices has gradually decreased, and the density of devices per unit volume has become higher and higher. When the equipment is working, the internal ambient temperature continues to rise, causing heat to accumulate rapidly. At this time, the effective heat dissipation of electronic devices is crucial to the safe operation of the entire system. In electronic products such as smart phones and tablets, thermal conductive structural adhesives are often needed. The common thermal conductive structural adhesive is polyurethane hot melt adhesive. Polyurethane hot melt adhesive is mainly composed of isocyanate-terminated oligomers. The isocyanate groups in the isocyanate-terminated oligomers can react with moisture in the air. After complete curing, a cross-linked chemical structure can be formed, thereby achieving high bonding strength. However, the covalent bonds obtained by the reaction of isocyanate groups with moisture are irreversible, and the cross-linked structure is difficult to be destroyed. After complete curing, it is usually difficult to disassemble the adhesive. If the bonded materials need to be separated, it is often necessary to use large external forces, high temperatures, chemical reagents and other conditions, and in the process of disassembling the adhesive, the bonded materials may be damaged, resulting in large economic losses.

[0003] In recent years, there is a technology that adds electrolyte salts to polyurethane hot melt adhesives to give polyurethane hot melt adhesives the function of being disassembled under power-on conditions. However, although the existing electrically detachable polyurethane hot melt adhesives can achieve the attenuation of bonding strength under power-on conditions, the thermal conductivity is low, which is not conducive to the application in structural bonding where the bonding parts are prone to heat and need to dissipate heat. If the heat is continuously difficult to dissipate, there may be a large safety hazard, and it cannot meet the bonding requirements with high requirements for heat dissipation performance. Since the components of polyurethane hot melt adhesives are mainly polymer materials, the thermal conductivity of polymer materials is poor. The existing thermal conductive polyurethane hot melt adhesives usually rely on adding thermal conductive fillers with excellent thermal conductivity to the adhesive components. By adding a high amount of thermal conductive fillers, the polyurethane hot melt adhesive is given a certain thermal conductivity. However, thermal conductive fillers are usually inorganic non-metallic materials. Inorganic materials have poor compatibility with polyurethane materials in organic systems. It is usually necessary to perform surface treatment modification on the thermal conductive fillers, and the corresponding adhesive materials also need to be modified. The prior art uses silane to completely block isocyanate and prepares silane-modified polyurethane adhesives with thermal conductivity in combination with thermal conductive fillers. However, the currently prepared thermal conductive silane-modified polyurethane adhesives still have a slow curing speed and require a long time of curing to establish a high bonding strength, which is not conducive to the rapid assembly of automated production lines. After complete curing, there is still a problem of difficulty in disassembly. In addition, the existing single-component polyurethane structural adhesive is prone to bubble problems during the curing process, which easily forms bonding defects and affects the bonding strength. At the same time, in thermal conductive bonding applications, bubbles will also form cavities to block the conduction of heat.

[0004] Therefore, there is an urgent need to develop an adhesive with good thermal conductivity, excellent bonding performance and electrical disassembly to meet the market demand for high-performance detachable thermally conductive adhesives. Summary of the invention

[0005] One of the purposes of the present invention is to provide a single-component silane-modified thermally conductive polyurethane hot melt adhesive which has good thermal conductivity, excellent bonding performance and can be disassembled by electricity.

[0006] A second object of the present invention is to provide a method for preparing the above-mentioned single-component silane-modified thermally conductive polyurethane hot melt adhesive.

[0007] The third object of the present invention is to provide the application of the above-mentioned single-component silane-modified thermally conductive polyurethane hot melt adhesive in the bonding of electronic products.

[0008] The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive provided by the present invention contains a siloxane-modified polyurethane prepolymer and a modified filler composition as well as an optional catalyst and a water absorbent. The modified filler composition contains a thermally conductive filler, an electrolyte salt, a silane coupling agent and an optional polar solvent compound. The content of isocyanate groups in the electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive is 0.2-0.8%, and the mass ratio of the siloxane-modified polyurethane prepolymer to the modified filler composition is 1:(1.5-7.5). The bonding strength of the electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive after being energized at a voltage of 1-100V is attenuated by more than 80%.

[0009] The preparation method of the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive provided by the present invention comprises uniformly mixing a siloxane-modified polyurethane prepolymer and a modified filler composition as well as an optional catalyst and a water absorbent to obtain the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive.

[0010] After in-depth and extensive research, the inventors of the present invention found that the reason why the existing one-component polyurethane hot melt adhesive has low bonding strength and poor thermal conductivity is mainly because: on the one hand, the existing one-component silane-terminated polyurethane adhesive is to completely terminate the isocyanate group by using a siloxane group. Although the use of siloxane to terminate the isocyanate is beneficial to improve the compatibility of the thermally conductive filler and the polymer adhesive, the speed of siloxane wet curing is much lower than the speed of isocyanate wet curing, and it usually takes a long time to be completely cured, and the bonding strength of siloxane after wet curing is also lower than the bonding strength of isocyanate after wet curing. On the other hand, the existing thermally conductive filler has poor compatibility with the electrically disassembled polyurethane hot melt adhesive. Directly adding the thermally conductive filler to the electrically disassembled polyurethane hot melt adhesive is likely to form defects at the interface between the thermally conductive filler and the polyurethane hot melt adhesive, which is not conducive to the formation of an effective thermal conductive network, thereby being not conducive to the realization of the thermal conductive function. On the other hand, the curing principle of existing polyurethane hot melt adhesives is that the residual isocyanate groups in the polyurethane hot melt adhesive chemically react with moisture in the air. However, the reaction between isocyanate and moisture will produce carbon dioxide gas, which is sometimes difficult to discharge when the adhesive layer is thick, and will form bubble cavities in the adhesive system. The formation of gas cavities will block the transfer of heat, thereby affecting the bonding performance and thermal conductivity of the adhesive.

[0011] The present invention innovatively utilizes electrolyte salt, silane coupling agent and optional polar solvent compound to pre-treat the surface of thermal conductive filler to obtain modified filler composition. At this time, not only can the compatibility of thermal conductive filler and polyurethane material be increased, but also the electrolyte salt introduced into the modified filler composition can provide the possibility of Faraday reaction of anion and cation under power-on condition. Introducing this modified filler composition into the adhesive system can give the adhesive the property of electrical disassembly. In addition, the present invention innovatively uses siloxane-modified polyurethane prepolymer as the main body. On the one hand, the moisture curing mechanism of siloxane is different from that of isocyanate. Siloxane will not generate bubbles during the curing process, which can greatly reduce the generation of bubbles during the curing process of the adhesive, avoid the formation of bonding defects due to bubbles and affect the bonding strength, and avoid the formation of cavities due to bubbles and block the heat conduction. Furthermore, controlling the content of isocyanate groups in the siloxane-modified polyurethane prepolymer within the scope of the present invention can well compensate for the defect of low bonding strength after moisture curing of siloxane, that is, the "bubble effect" avoided by siloxane and the post-curing thickening of specific isocyanate groups can effectively give the adhesive good bonding strength; on the other hand, the siloxane-modified polyurethane prepolymer has higher compatibility with thermally conductive fillers, greatly increases the compatibility between thermally conductive fillers and organic polymer adhesives, and can effectively volatilize the thermal conductivity of the thermally conductive fillers, that is, the "bubble cavity heat resistance" avoided by siloxane and the volume expansion of siloxane can effectively give the adhesive good thermal conductivity. In summary, the one-component silane-modified thermally conductive polyurethane hot melt adhesive provided by the present invention has the advantages of good thermal conductivity, excellent bonding performance and can be disassembled when powered on, and has broad practical application prospects. DETAILED DESCRIPTION

[0012] The electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive provided by the present invention has a bonding strength attenuation rate of more than 80% after being energized at a voltage of 1 to 100 V, and can specifically be 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 99%, 100% or any value therebetween. The voltage required for electrical disassembly of the electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive is preferably 1 to 100 V, and can specifically be 1 V, 3 V, 5 V, 7 V, 9 V, 10 V, 20 V, 30 V, 40 V, 50 V, 60 V, 70 V, 80 V, 90 V, 100 V or any value therebetween; the time required for electrical disassembly is preferably 1 s to 60 min, such as 1 s, 2 s, 5 s, 15 s, 30 s, 40 s, 50 s, 1 min, 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min or any value therebetween. The content of isocyanate groups in the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive is 0.2-0.8%, specifically 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or any value therebetween.

[0013] The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive provided by the present invention contains a siloxane-modified polyurethane prepolymer and a modified filler composition and an optional catalyst and a water absorbent. Wherein, based on the total weight of the electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, the total content of the siloxane-modified polyurethane prepolymer and the modified filler composition is preferably 90-99.8%, the content of the catalyst is preferably 0.1-5%, and the content of the water absorbent is preferably 0.1-5%. Specifically, the total content of the siloxane-modified polyurethane prepolymer and the modified filler composition is preferably 90%, 92%, 94%, 96%, 98%, 99%, 99.5%, 99.8% or any value therebetween. The content of the catalyst and the water absorbent is preferably independently 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or any value therebetween. The mass ratio of the siloxane-modified polyurethane prepolymer to the modified filler composition is preferably 1:(1.5-7.5), specifically 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5 or any value therebetween.

[0014] In the present invention, the siloxane-modified polyurethane prepolymer can be obtained by commercial purchase or prepared according to various existing methods. In a preferred embodiment, the siloxane-modified polyurethane prepolymer is prepared according to the following method: S11, a polyol compound and a polyisocyanate compound are subjected to a first addition reaction optionally in the presence of a catalyst to obtain an isocyanate-diblocked polyurethane prepolymer; S12, the isocyanate-diblocked polyurethane prepolymer is subjected to a second addition reaction with a monomercaptosilane compound to obtain a siloxane-modified polyurethane prepolymer.

[0015] In the preparation process of the above-mentioned siloxane-modified polyurethane prepolymer, the molar ratio of the hydroxyl group in the polyol compound, the isocyanate group in the polyisocyanate compound and the mercapto group in the monomercaptosiloxane compound is preferably 1:(2-2.5):(0.3-0.9). At this time, the prepared siloxane-modified polyurethane prepolymer not only has lower bubbles and good compatibility with thermally conductive fillers, can provide good thermal conductivity, but also has excellent bonding properties and a faster curing speed. Specifically, based on 1 mol of hydroxyl group in the polyol compound, the content of isocyanate group in the polyisocyanate compound is preferably 2.0-2.5 mol, such as 2.0 mol, 2.1 mol, 2.2 mol, 2.3 mol, 2.4 mol, 2.5 mol or any value therebetween; the content of mercapto group in the monomercaptosiloxane compound is preferably 0.3-0.9 mol, such as 0.3 mol, 0.4 mol, 0.5 mol, 0.6 mol, 0.7 mol, 0.8 mol, 0.9 mol or any value therebetween.

[0016] In the preparation process of the above-mentioned siloxane-modified polyurethane prepolymer, the polyol compound can use various known polyol compounds commonly used in polyurethane manufacturing, such as at least one of polyester polyol, polyether polyol, polycarbonate polyol, polyalkylene polyol, etc. These polyol compounds can be used alone or in combination of two or more. The number average molecular weight of the polyol compound is preferably 1000 to 4000 g / mol, specifically 1000, 1500, 2000, 2500, 3000, 3500, 4000 g / mol or any value therebetween.

[0017] The polyester polyol may be a polyester polyol obtained by reacting a polycarboxylic acid with a polyol or a poly-ε-caprolactone polyol obtained by ring-opening polymerization of ε-caprolactone. The polycarboxylic acid may be at least one of terephthalic acid, isophthalic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decamethylene dicarboxylic acid, and dodecamethylene dicarboxylic acid. The polyol may be at least one of ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, and cyclohexanediol.

[0018] The polyether polyol can be selected from the ring-opening polymer of ethylene glycol, propylene glycol, tetrahydrofuran, 3-methyltetrahydrofuran, or a random copolymer or block copolymer of ethylene glycol, propylene glycol, tetrahydrofuran, 3-methyltetrahydrofuran or its derivatives, or a mixture of at least one of the above polyoxyalkylene modified bodies of bisphenol type. The polyoxyalkylene modified body of bisphenol type is a polyether polyol obtained by adding alkylene oxide to the active hydrogen part of the bisphenol type molecular skeleton, and can be a random copolymer or a block copolymer. The alkylene oxide can be selected from at least one of ethylene oxide, propylene oxide, butylene oxide and isobutylene oxide.

[0019] The polycarbonate polyol can be selected from at least one of polycarbonate 1,6-hexanediol ester polyol, polycarbonate-1,4-butanediol-1,6-hexanediol ester diol, polycarbonate-1,5-pentanediol-1,6-hexanediol ester diol, polycaprolactone hexanediol, polycarbonate-1,4-cyclohexanedimethanol-1,6-hexanediol ester diol, polyethylene carbonate diol, polypropylene carbonate diol, polybutylene carbonate diol, and polyhexylene carbonate diol.

[0020] The polyalkylene polyol may be selected from at least one of polybutadiene polyol, hydrogenated polybutadiene polyol and hydrogenated polyisoprene polyol.

[0021] In the preparation process of the above-mentioned siloxane-modified polyurethane prepolymer, the polyisocyanate compound can be selected from at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, xylene diisocyanate, tetramethylxylene diisocyanate, norbornane diisocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate.

[0022] In the preparation process of the above-mentioned siloxane-modified polyurethane prepolymer, the monomercaptosiloxane compound can be selected from at least one of 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropylmethyldiethoxysilane.

[0023] In the preparation process of the above-mentioned siloxane-modified polyurethane prepolymer, the conditions of the first addition reaction and the second addition reaction independently include a temperature of preferably 70 to 90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; and a time of preferably 1 to 5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween.

[0024] In the present invention, the modified filler composition contains a thermally conductive filler, an electrolyte salt, a silane coupling agent, and an optional polar solvent compound. The content of the thermally conductive filler is preferably 70 to 85 parts by weight, such as 70, 72, 75, 78, 80, 82, 85 parts by weight or any value therebetween; the content of the electrolyte salt is preferably 5 to 15 parts by weight, such as 5, 8, 10, 12, 15 parts by weight or any value therebetween; the content of the silane coupling agent is preferably 2 to 7 parts by weight, such as 2, 3, 4, 5, 6, 7 parts by weight or any value therebetween; the content of the polar solvent compound is 0 to 15 parts by weight, such as 0, 1, 3, 5, 7, 9, 11, 13, 15 parts by weight or any value therebetween.

[0025] In the present invention, the thermally conductive filler is mainly an inorganic substance, and the thermally conductive filler is first modified with an electrolyte salt, a silane coupling agent, and an optional polar solvent compound. Among them, the siloxane in the silane coupling agent can perform surface modification on the inorganic thermally conductive filler, and the siloxane end of the silane coupling agent has good adhesion to the inorganic thermally conductive filler. The organic functional groups at the other end of the silane coupling agent, such as mercapto, epoxy, isocyanate, etc., have good compatibility with the organic polymer in the adhesive, and the coupling effect can promote the subsequent mixing with the adhesive components to improve the compatibility. Among them, before adding the thermally conductive filler to the adhesive, pre-modifying the thermally conductive filler has two functions. On the one hand, the surface of the inorganic thermally conductive filler can be fully modified using a silane coupling agent in advance; on the other hand, it also has the function of removing residual moisture in the components such as solvents, fillers, and electrolyte salts in the modified filler composition, thereby avoiding the influence of moisture in the next step of mixing with the adhesive and causing side reactions. That is, the pre-mixing process can make the inorganic thermally conductive filler more fully mixed and modified, and remove water more thoroughly, thereby improving the compatibility of the thermally conductive filler and the adhesive. In addition, the polar solvent compound can be used as a dispersion and mixing medium for the thermally conductive filler, the silane coupling agent and the electrolyte salt.

[0026] The modified filler composition can be obtained by mixing a thermally conductive filler, an electrolyte salt, a silane coupling agent, and an optional polar solvent compound in any manner. In a preferred embodiment, the modified filler composition is prepared according to the following method: S21, the electrolyte salt, the silane coupling agent, and the optional polar solvent compound are vacuum stirred and dehydrated at 100-120°C at a speed of 100-200 r / min for 1-5 hours to obtain a pretreated product; S22, the pretreated product and the thermally conductive filler are vacuum stirred and reacted at 100-120°C at a speed of 100-200 r / min for 3-6 hours to obtain a modified filler composition.

[0027] In the preparation process of the modified filler composition, in step S21, the temperature of the vacuum stirring dehydration is 100-120°C, such as 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C or any value therebetween; the rotation speed is 100-200r / min, such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200r / min or any value therebetween; and the time is 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween.

[0028] In the preparation process of the modified filler composition, in step S22, the temperature of the vacuum stirring reaction is 100-120°C, such as 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C or any value therebetween; the rotation speed is 100-200r / min, such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200r / min or any value therebetween; and the time is 3-6h, such as 3h, 4h, 5h, 6h or any value therebetween.

[0029] In the present invention, the thermally conductive filler may be at least one of aluminum oxide, magnesium oxide, zinc oxide, nickel oxide, aluminum nitride, silicon nitride, boron nitride, and silicon carbide. In addition, the particle size of the thermally conductive filler is preferably 1 nm to 100 μm, such as 1 nm, 50 nm, 100 nm, 500 nm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, or any value therebetween.

[0030] In the present invention, the electrolyte salt can be an alkali metal salt and / or an ionic liquid. Wherein, the alkali metal salt can be a salt composed of an alkali metal cation and an organic acid anion or an inorganic acid anion or an organic sulfonyl imide anion, such as lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium chloride, lithium sulfate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroantimonate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium chloride, sodium sulfate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium hexafluoroantimonate, potassium trifluoromethanesulfonate, potassium bistrifluoromethanesulfonyl imide, potassium chloride, potassium sulfate, potassium tetrafluoroborate, potassium hexafluorophosphate, potassium hexafluoroantimonate. The ionic liquid is a liquid molten salt at room temperature (25°C) and can be composed of organic cations and anions. Specific examples of the organic cations include, but are not limited to, imidazole cations, pyrrole cations, quaternary ammonium salt cations, quaternary phosphonium salt cations, pyrrolidine cations, and piperidine cations. Specific examples of the anion include, but are not limited to, trifluoromethanesulfonate anion, tetrafluoroborate anion, hexafluorophosphate anion, bisfluoromethanesulfonimide anion, hydrogen sulfate anion, ethyl sulfate anion, and p-toluenesulfonate anion. Specific examples of the ionic liquid may include, but are not limited to, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-2,3-dimethylimidazolium trifluoromethanesulfonate, 1-octyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-2,3-dimethylimidazolium tetrafluoroborate, 1-propyl-2,3-methylimidazolium tetrafluoroborate, 1-butyl-2,3-dimethylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-2,3-dimethylimidazolium ethyl sulfate, 1-butyl-3-methylimidazolium tetrafluoroborate ...propyl-2,3-methylimidazolium tetrafluoroborate, 1-butyl-2,3-dimethylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl at least one of imidazolium bis(trifluoromethanesulfonyl)imide salt, 1,3-diethylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1,2-dimethyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salt, N-butylpyridinium tetrafluoroborate, hexyltriethylammonium bis(trifluoromethanesulfonyl)imide salt, methyltrioctylphosphonium bis(trifluoromethanesulfonyl)imide salt, N-butyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, N-butyl-N-methylpyrrolidine trifluoromethanesulfonate salt, and N-propyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide salt.

[0031] In the present invention, specific examples of the silane coupling agent include, but are not limited to: 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, At least one of 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-isocyanatepropyltrimethoxysilane.

[0032] In the present invention, the polar solvent compound can be selected from at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, dimethoxymethane, 1,3-dimethoxypropane, 1,3-dioxolane, ethoxymethoxyethane, poly(ethylene glycol) dimethyl ether, poly(ethylene glycol) methyl ether methacrylate, poly(ethylene glycol) methyl ether, poly(ethylene glycol) methyl ether acrylate, poly(ethylene glycol) diglycidyl ether, poly(ethylene glycol) ethyl ether methacrylate, polyethylene glycol-bis(2-ethylhexanoate), poly(ethylene glycol) octyl ether, poly(ethylene glycol) phenyl ether acrylate, poly(ethylene glycol) tetrahydrofurfuryl ether, and poly(ethylene glycol) methyl ether toluene sulfonate.

[0033] In the present invention, the catalyst may be at least one of dibutyltin dilaurate, stannous octoate, zinc isooctanoate, bismuth isooctanoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine, and 2,2-dimorpholinyl diethyl ether.

[0034] In the present invention, the water absorbent may be at least one of a molecular sieve desiccant, an oxazolidine desiccant, p-toluenesulfonyl isocyanate and triethyl orthoformate.

[0035] The preparation method of the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive provided by the present invention comprises uniformly mixing a siloxane-modified polyurethane prepolymer and a modified filler composition as well as an optional catalyst and a water absorbent to obtain the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive.

[0036] The present invention has no particular limitation on the mixing method, and the materials can be added and mixed in any order. In a preferred embodiment, the mixing step includes:

[0037] S31, dehydrating the polyol compound and the optional water absorbent at 100-120° C. and 100-200 r / min under vacuum stirring for 1-5 h, and then cooling to 70-90° C. to obtain a pretreated product;

[0038] S32, adding a polyisocyanate compound and an optional catalyst to the pretreated product, stirring the mixture in a vacuum at 70 to 90° C. and at a speed of 100 to 200 r / min for 1 to 5 hours to obtain an isocyanate-diblocked polyurethane prepolymer;

[0039] S33, reacting the isocyanate-dicapped polyurethane prepolymer with the monomercaptosilane compound under vacuum stirring at 70 to 90° C. and at a speed of 100 to 200 r / min for 1 to 5 hours to obtain a siloxane-modified polyurethane prepolymer;

[0040] S34, reacting the siloxane-modified polyurethane prepolymer and the modified filler composition at 70-90° C. and at a rotation speed of 100-200 r / min with vacuum stirring for 0.5-2 h to obtain an electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive.

[0041] In the preparation process of the above-mentioned electrically detachable one-component silicone-modified thermally conductive polyurethane hot melt adhesive, in step S31, the temperature of the vacuum stirring dehydration is 100-120°C, such as 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C or any value therebetween; the rotation speed is 100-200r / min, such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200r / min or any value therebetween; the time is 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween.

[0042] In the preparation process of the above-mentioned electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, in step S32, the temperature of the vacuum stirring reaction is 70-90°C, such as 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C or any value therebetween; the rotation speed is 100-200r / min, such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200r / min or any value therebetween; the time is 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween.

[0043] In the preparation process of the above-mentioned electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, in step S33, the temperature of the vacuum stirring reaction is 70-90°C, such as 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C or any value therebetween; the rotation speed is 100-200r / min, such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200r / min or any value therebetween; the time is 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween.

[0044] In the preparation process of the above-mentioned electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, in step S34, the temperature of the vacuum stirring reaction is 70-90°C, such as 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C or any value therebetween; the rotation speed is 100-200r / min, such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200r / min or any value therebetween; the time is 0.5-2h, such as 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h or any value therebetween.

[0045] The present invention also provides application of the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive in bonding electronic products.

[0046] The present invention will be described in detail below through examples.

[0047] The bonding substrate applicable to the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive provided by the present invention is a conductive substrate.

[0048] The present invention will be described in detail below through examples and comparative examples.

[0049] In the following examples and comparative examples, the parts of each raw material are parts by weight.

[0050] Preparation Example 1 Modified filler composition

[0051] In parts by weight, 9.88 parts of 1-propyl-3-methylimidazole tetrafluoroborate, 6.17 parts of propylene carbonate, and 3.70 parts of 3-aminopropyltrimethoxysilane were added to a reactor, heated to 110°C, and vacuum dehydrated for 2 hours under stirring conditions at 150 r / min. 40.25 parts of aluminum oxide with a particle size of 8-10 μm (Foshan Weiked Materials, GTC-21K) and 40.0 parts of magnesium oxide with a particle size of 30-50 nm (Hangzhou Hengna New Materials, HN-Mg50D) were added to the reactor, and vacuum dehydrated for 4 hours under stirring and mixing conditions at 110°C and 150 r / min to obtain a modified filler composition A-1, which was vacuum sealed and stored for later use.

[0052] Preparation Example 2 Modified Filler Composition

[0053] By weight, 11.90 parts of 1-propyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt and 4.0 parts of 3-glycidoxypropyltrimethoxysilane were added to a reactor, heated to 110°C, and vacuum dehydrated for 2 hours at 150 r / min stirring conditions. 63.33 parts of alumina with a particle size of 6-9 μm (Foshan Weiked Materials, GTC-31K) and 20.0 parts of boron nitride with a particle size of 60-75 μm (Shanghai Baitu, GBN-60) were added to the reactor, and vacuum dehydrated for 4 hours at 110°C and 150 r / min stirring and mixing conditions to obtain a modified filler composition A-2, which was vacuum sealed and stored for later use.

[0054] Preparation Example 3 Modified Filler Composition

[0055] In parts by weight, 7.69 parts of hexyltriethylammonium bis(trifluoromethanesulfonyl)imide salt, 4.62 parts of poly(ethylene glycol) diglycidyl ether, and 3.08 parts of vinyltrimethoxysilane were added to a reactor, heated to 110°C, and vacuum dehydrated for 2 hours at 150 r / min stirring conditions. 34.32 parts of alumina with a particle size of 8-10 μm (Foshan Weiked Materials, GTC-066B) and 50.30 parts of alumina with a particle size of 2.5-4.0 μm (Foshan Weiked Materials, DR-50) were added to the reactor, and vacuum dehydrated for 4 hours at 110°C and 150 r / min stirring and mixing conditions to obtain a modified filler composition A-3, which was vacuum sealed and stored for later use.

[0056] Preparation Example 4 Modified Filler Composition

[0057] In parts by weight, 6.82 parts of lithium bis(trifluoromethanesulfonyl)imide, 11.36 parts of ethylene carbonate, and 5.68 parts of 3-isocyanatepropyltrimethoxysilane were added to a reactor, heated to 110°C, and vacuum dehydrated for 2 hours under stirring conditions at 150 r / min. 33.12 parts of magnesium oxide with a particle size of 30-50 nm (Hangzhou Hengna New Materials, HN-Mg50D) and 43.02 parts of aluminum oxide with a particle size of 8-10 μm (Foshan Weikede Materials, GTC-066B) were added to the reactor, and vacuum dehydrated for 4 hours under stirring and mixing conditions at 110°C and 150 r / min to obtain a modified filler composition A-4, which was vacuum sealed and stored for later use.

[0058] Preparation Example 5 Modified Filler Composition

[0059] By weight, 8.86 parts of lithium tetrafluoroborate, 10.13 parts of polyethylene glycol-bis(2-ethylhexanoate), and 5.06 parts of 3-mercaptopropyltrimethoxysilane were added to a reactor, heated to 110°C, and vacuum dehydrated for 2 hours at 150 r / min stirring conditions. 60.53 parts of aluminum oxide with a particle size of 8-10 μm (Foshan Weiked Materials, GTC-21K) and 15.42 parts of boron nitride with a particle size of 60-75 μm (Shanghai Baitu, GBN-60) were added to the reactor, and vacuum dehydrated for 4 hours at 110°C and 150 r / min stirring and mixing conditions to obtain a modified filler composition A-5, which was vacuum sealed and stored for later use.

[0060] Comparative Preparation Example 1 Modified Filler Composition

[0061] The modified filler composition was prepared in the same manner as in Preparation Example 3, except that the hexyltriethylammonium bis(trifluoromethanesulfonyl)imide salt in Preparation Example 3 was removed, as follows:

[0062] In parts by weight, 4.62 parts of poly(ethylene glycol) diglycidyl ether and 3.08 parts of vinyltrimethoxysilane were added to a reactor, heated to 110°C, and vacuum dehydrated for 2 hours under stirring conditions at 150 r / min. 34.32 parts of alumina with a particle size of 8-10 μm (Foshan Weiked Materials, GTC-066B) and 50.30 parts of alumina with a particle size of 2.5-4.0 μm (Foshan Weiked Materials, DR-50) were added to the reactor, and vacuum dehydrated for 4 hours under stirring and mixing conditions at 110°C and 150 r / min to obtain a modified filler composition C-1, which was vacuum sealed and stored for later use.

[0063] Comparative Preparation Example 2 Modified Filler Composition

[0064] A modified filler composition was prepared in the same manner as in Preparation Example 1, except that the 3-aminopropyltrimethoxysilane in Preparation Example 1 was removed, as follows:

[0065] By weight, 9.88 parts of 1-propyl-3-methylimidazole tetrafluoroborate and 6.17 parts of propylene carbonate were added to the reactor, heated to 110°C, and vacuum dehydrated for 2 hours under stirring conditions at 150 r / min. 40.25 parts of aluminum oxide with a particle size of 8-10 μm (Foshan Weikede Materials, GTC-21K) and 40.0 parts of magnesium oxide with a particle size of 30-50 nm (Hangzhou Hengna New Materials, HN-Mg50D) were added to the reactor, and vacuum dehydrated for 4 hours under stirring and mixing conditions at 110°C and 150 r / min to obtain a modified filler composition C-2, which was vacuum sealed and stored for later use.

[0066] Example 1

[0067] By weight, 4.88 g (9.763 mmol) of polyhexamethylene adipate diol with a number average molecular weight of 1000, 4.88 g (9.763 mmol) of polyoxypropylene ether diol with a number average molecular weight of 1000, and 0.5 g of water absorbent additive were added. TI, heated to 110°C, vacuum dehydrated for 2h under stirring conditions of 150r / min; then cooled to 80°C, added 5.86g (46.863mmol) of 4,4'-diphenylmethane diisocyanate (MDI) and 0.2g of stannous octoate, reacted for 2h under stirring conditions of 150r / min, added 2.68g (13.668mmol) of 3-mercaptopropyltrimethylsilane, reacted for 2h under vacuum stirring at 80°C and 150r / min, added 81.0g of modified filler composition A1, mixed under vacuum stirring at 80°C and 150r / min for 1h, and then discharged to obtain an electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, wherein the isocyanate group content is 0.57%, and stored in a vacuum sealed state.

[0068] Example 2

[0069] By weight, 4.09 g (8.185 mmol) of polybutylene adipate diol with a number average molecular weight of 1000, 4.09 g (8.185 mmol) of polytetramethylene glycol with a number average molecular weight of 1000, and 0.2 g of water absorbent additive were added. OF, heated to 110°C, vacuum dehydrated for 2h under stirring conditions of 150r / min; then cooled to 80°C, added 5.36g (40.927mmol) of 4,4-diisocyanate dicyclohexylmethane (HMDI) and 0.5g of dibutyltin dilaurate, reacted for 2h under stirring conditions of 150r / min, added 1.75g ​​(7.367mmol) of 3-mercaptopropyltriethoxysilane, reacted for 2h under vacuum stirring at 80°C and 150r / min, added 84.0g of modified filler composition A2, mixed under vacuum stirring at 80°C and 150r / min for 1h, and then discharged to obtain an electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, wherein the isocyanate group content is 0.72%, and stored in a vacuum sealed state.

[0070] Example 3

[0071] By weight, 14.27 g (4.758 mmol) of polytetramethylene ether diol with a number average molecular weight of 3000, 14.27 g (4.758 mmol) of polycaprolactone diol with a number average molecular weight of 2000, and 0.6 g of water absorbent Siliporite SA1702 were heated to 110° C. and vacuum-dehydrated for 2 h at 150 r / min stirring; then cooled to 80° C., 3.52 g (20.936 mmol) of hexamethylene diisocyanate (HDI), 1.1 g 2,2-dimorpholinyl diethyl ether was reacted under stirring conditions at 150 r / min for 2 h, 1.23 g (6.852 mmol) of 3-mercaptopropylmethyldimethoxysilane was added, and the mixture was stirred under vacuum at 80 ° C and 150 r / min for 2 h. Then, 65.0 g of modified filler composition A3 was added, and the mixture was stirred under vacuum at 80 ° C and 150 r / min for 1 h, and then the material was discharged to obtain an electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, wherein the isocyanate group content was 0.67%, and the adhesive was stored in a vacuum sealed state.

[0072] Example 4

[0073] By weight, 3.09 g (3.086 mmol) of polycarbonate 1,6 hexanediol with a number average molecular weight of 1000, 3.09 g (3.086 mmol) of polybutylene adipate diol with a number average molecular weight of 1000, and 0.2 g of water absorbent additive were added. TI, heated to 110°C, vacuum dehydrated for 2h under stirring conditions at 150r / min; then cooled to 80°C, added 2.74g (12.345mmol) of isophorone diisocyanate (IPDI) and 1.3g of zinc isooctanoate, reacted for 2h under stirring conditions at 150r / min, added 1.59g (6.667mmol) of 3-mercaptopropyltriethoxysilane, reacted for 2h under vacuum stirring at 80°C and 150r / min, added 88.0g of modified filler composition A4, mixed under vacuum stirring at 80°C and 150r / min for 1h, and then discharged to obtain an electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, wherein the isocyanate group content is 0.24%, and stored in a vacuum sealed state.

[0074] Example 5

[0075] By weight, 7.57 g (3.783 mmol) of polybutylene succinate diol with a number average molecular weight of 2000, 7.57 g (3.783 mmol) of polycaprolactone diol with a number average molecular weight of 2000, and 0.4 g of water absorbent additive were added. OF, heated to 110°C, vacuum dehydrated for 2 hours under stirring conditions of 150r / min; then cooled to 80°C, added 3.78g (15.134mmol) of 4,4'-diphenylmethane diisocyanate (MDI) and 0.2g of bismuth isooctanoate, reacted for 2 hours under stirring conditions of 150r / min, added 1.48g (7.567mmol) of 3-mercaptopropyltrimethylsilane, reacted for 2 hours under vacuum stirring at 80°C and 150r / min, added 79.0g of modified filler composition A5, mixed under vacuum stirring at 80°C and 150r / min for 1 hour, and then discharged to obtain an electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, wherein the isocyanate group content is 0.32%, and stored in a vacuum sealed state.

[0076] Comparative Example 1

[0077] By weight, 29.2 g (14.6 mmol) of polyoxypropylene ether diol with a number average molecular weight of 2000, 29.2 g (14.6 mmol) of polyhexane adipate diol with a number average molecular weight of 2000, 8.0 g of lithium trifluoromethanesulfonate, 8.0 g of propylene carbonate, 10.0 g of acrylic resin BR113, 0.5 g of water absorbent Additive OF, 0.5 g of 3-Aminopropyltrimethoxysilane was heated to 110°C and vacuum dehydrated for 2 h at 150 r / min stirring conditions; then the temperature was lowered to 80°C, 14.6 g (58.4 mmol) of 4,4'-diphenylmethane diisocyanate (MDI) and 0.2 g of dibutyltin dilaurate were added, and the reaction was carried out at 150 r / min stirring conditions for 2 h before discharging the material to obtain a reference electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, in which the isocyanate group content was 2.45%, and the adhesive was stored in a vacuum sealed state.

[0078] Comparative Example 2

[0079] An electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive was prepared in the manner of Example 3, except that the electrolyte salt in Example 3 was removed, as follows:

[0080] By weight, 14.27 g (4.758 mmol) of polytetramethylene ether diol with a number average molecular weight of 3000, 14.27 g (4.758 mmol) of polycaprolactone diol with a number average molecular weight of 2000, and 0.6 g of water absorbent Siliporite SA1702 were heated to 110° C. and vacuum-dehydrated for 2 h at 150 r / min stirring; then cooled to 80° C., 3.52 g (20.936 mmol) of hexamethylene diisocyanate (HDI), 1.1 g 2,2-dimorpholinyl diethyl ether was reacted under stirring conditions at 150 r / min for 2 h, 1.23 g (6.852 mmol) of 3-mercaptopropylmethyldimethoxysilane was added, and the mixture was stirred under vacuum at 80 ° C and 150 r / min for 2 h. Then, 65.0 g of the modified filler composition C1 was added, and the mixture was stirred under vacuum at 80 ° C and 150 r / min for 1 h, and then the material was discharged to obtain a reference single-component siloxane-modified thermally conductive polyurethane hot melt adhesive, in which the content of isocyanate groups was 0.67%, and the adhesive was stored in a vacuum sealed state.

[0081] Comparative Example 3

[0082] An electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive was prepared in the manner of Example 3, except that the components of the modified filler composition in Example 3 were directly added to the adhesive system, as follows:

[0083] By weight, 14.27 g (4.758 mmol) of polytetramethylene ether diol with a number average molecular weight of 3000, 14.27 g (4.758 mmol) of polycaprolactone diol with a number average molecular weight of 2000, and 0.6 g of water absorbent Siliporite SA1702 were heated to 110° C. and vacuum dehydrated for 2 h under stirring conditions of 150 r / min; then the temperature was lowered to 80° C., 3.52 g (20.936 mmol) of hexamethylene diisocyanate (HDI), 1.1 g 2,2-dimorpholinyl diethyl ether was stirred at 150 r / min for 2 h, 1.23 g (6.852 mmol) of 3-mercaptopropylmethyldimethoxysilane was added, and the mixture was stirred at 80 ° C and 150 r / min for 2 h in vacuum, and then 5.0 g of hexyltriethylammonium bis(trifluoromethanesulfonyl)imide salt, 3.0 g of poly(ethylene glycol) diglycidyl ether, and 2.0 g of vinyltrimethoxysilane were added to the reactor, heated to 110 ° C, and stirred at 150 r / min for 2 h. / min stirring conditions for vacuum dehydration for 2h, 22.31g of alumina with a particle size of 8-10μm (Foshan Weikede Materials, GTC-066B) and 32.69g of alumina with a particle size of 2.5-4.0μm (Foshan Weikede Materials, DR-50) were mixed under vacuum stirring at 80°C and 150r / min for 1h and then discharged to obtain a reference single-component siloxane-modified thermally conductive polyurethane hot melt adhesive with an isocyanate group content of 0.67%, which was vacuum sealed and stored.

[0084] Comparative Example 4

[0085] An electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive is prepared in the manner of Example 1, except that the proportion of the end-modified mercaptosiloxane component in the siloxane-end-modified prepolymer is reduced so that the content of isocyanate groups in the obtained electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive exceeds 0.8%, as follows:

[0086] By weight, 5.62 g (11.245 mmol) of polyhexamethylene adipate diol with a number average molecular weight of 1000, 5.62 g (11.245 mmol) of polyoxypropylene ether diol with a number average molecular weight of 1000, and 0.5 g of water absorbent additive were added. TI, heated to 110°C, vacuum dehydrated for 2h under stirring conditions of 150r / min; then cooled to 80°C, added 6.75g (53.974mmol) of 4,4'-diphenylmethane diisocyanate (MDI) and 0.2g of stannous octoate, reacted for 2h under stirring conditions of 150r / min, added 0.31g (1.574mmol) of 3-mercaptopropyltrimethylsilane, reacted for 2h under vacuum stirring at 80°C and 150r / min, added 81.0g of modified filler composition A1, mixed under vacuum stirring at 80°C and 150r / min for 1h, and then discharged to obtain a reference electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, wherein the isocyanate group content is 1.26%, and stored in a vacuum sealed state.

[0087] Comparative Example 5

[0088] An electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive was prepared in the manner of Example 1, except that the 3-aminopropyltrimethoxysilane in Example 1 was removed, as follows:

[0089] By weight, 4.88 g (9.763 mmol) of polyhexamethylene adipate diol with a number average molecular weight of 1000, 4.88 g (9.763 mmol) of polyoxypropylene ether diol with a number average molecular weight of 1000, and 0.5 g of water absorbent additive were added. TI, heated to 110°C, vacuum dehydrated for 2h under stirring conditions of 150r / min; then cooled to 80°C, added 5.86g (46.863mmol) of 4,4'-diphenylmethane diisocyanate (MDI) and 0.2g of stannous octoate, reacted for 2h under stirring conditions of 150r / min, added 2.68g (13.668mmol) of 3-mercaptopropyltrimethylsilane, reacted for 2h under vacuum stirring at 80°C and 150r / min, added 81.0g of modified filler composition C2, mixed under vacuum stirring at 80°C and 150r / min for 1h, and then discharged to obtain a reference electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, wherein the isocyanate group content is 0.57%, and stored in a vacuum sealed state.

[0090] Test Case

[0091] (1) Curing bubble performance: The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive obtained in the examples and comparative examples was melted at 110°C. After melting, a film was coated on the release film using a 400 μm scraper. The film was placed in an oven at 25°C and 50 RH% for curing for 4 hours. The appearance of the film was observed and whether bubbles were generated in the film was recorded. The results are shown in Table 1.

[0092] (2) Bonding strength at different curing times (1h, 1d, 7d): The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive obtained in the examples and comparative examples was dispensed at 110°C using a dispensing machine, and a rectangular adhesive line of 25mm*4mm was applied on the stainless steel substrate. Then, another stainless steel substrate was bonded to the stainless steel substrate. After bonding, the sample was cured in an environment of 25°C and 50% RH for 1h, 1d, and 7d. Then, the prepared bonding sample was run at a speed of 10mm / min along the shear direction using a universal material testing machine until the sample failed to bond. The maximum force value displayed by the recording instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after different curing times was calculated in combination with the bonding area. The results are shown in Table 1.

[0093] (3) Bonding strength after power-on: Use a glue dispenser to dispense the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive obtained in the embodiment and the comparative example at 110°C, apply a rectangular glue line of 25mm*4mm on the stainless steel substrate, and then bond another stainless steel substrate to the stainless steel substrate. After bonding, cure the sample in an environment of 25°C and 50%RH for 48h, and then clamp the positive and negative wires of the DC power supply at both ends of the shear sample, respectively, and power on for a certain period of time at a certain voltage. After power-on is completed, remove the shear sample, use a universal material testing machine to run the prepared bonding sample along the shear direction at a speed of 10mm / min until the sample fails to bond, record the maximum force value displayed by the instrument, and calculate the shear bonding strength of the adhesive to the stainless steel substrate after power-on in combination with the bonding area. The results are shown in Table 1.

[0094] (4) Thermal conductivity: The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive obtained in the examples and comparative examples was coated on a clean PET film and cured for 7 days in an environment of 25°C and 50% RH. The thermal conductivity was then tested according to the method of the national standard GB / T11205-2009.

[0095] Table 1

[0096]

[0097] It can be seen from the results in Table 1 that the electrically detachable one-component silicone-modified thermally conductive polyurethane hot melt adhesive provided by the present invention is bubble-free and has a high thermal conductivity, which is conducive to faster heat transfer of the adhesive, thereby helping the bonded components to achieve the function of rapid heat dissipation and reducing the impact of a sharp increase in heat on the operability and safety of electronic components. According to practical experience, if the bonding strength at room temperature is below 2.0MPa, it means that the adhesive is detachable, otherwise it is not detachable. It can be seen from the results in Table 1 that after the electrically detachable one-component silicone-modified thermally conductive polyurethane hot melt adhesive provided by the present invention is energized, the bonding strength can be significantly attenuated, and it can even fall off directly, and has excellent energized disassembly performance.

[0098] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. An electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive, characterized in that: The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive contains a siloxane-modified polyurethane prepolymer and a modified filler composition as well as an optional catalyst and a water absorbent. The modified filler composition contains a thermally conductive filler, an electrolyte salt, a silane coupling agent and an optional polar solvent compound. The content of isocyanate groups in the electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive is 0.2-0.8%, and the mass ratio of the siloxane-modified polyurethane prepolymer to the modified filler composition is 1:(1.5-7.5). The bonding strength of the electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive after being energized at a voltage of 1-100V is attenuated by more than 80%.

2. The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to claim 1, characterized in that: Based on the total weight of the electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive, the total content of the siloxane-modified polyurethane prepolymer and the modified filler composition is 90-99.8%, the content of the catalyst is 0.1-5%, and the content of the water absorbent is 0.1-5%.

3. The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to claim 1, characterized in that: The siloxane-modified polyurethane prepolymer is prepared according to the following method: S11, optionally subjecting a polyol compound and a polyisocyanate compound to a first addition reaction in the presence of a catalyst to obtain an isocyanate-diblocked polyurethane prepolymer; S12, subjecting the isocyanate-dicapped polyurethane prepolymer to a second addition reaction with a monomercaptosilane compound to obtain a siloxane-modified polyurethane prepolymer.

4. The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to claim 3, characterized in that: The molar ratio of the hydroxyl group in the polyol compound, the isocyanate group in the polyisocyanate compound and the mercapto group in the monomercaptosiloxane compound is 1:(2-2.5):(0.3-0.9); Preferably, the polyol compound is selected from at least one of polyester polyol, polyether polyol, polycarbonate polyol and polyalkylene polyol; Preferably, the polyisocyanate compound is selected from at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, xylylene diisocyanate, tetramethylxylene diisocyanate, norbornane dimethylene isocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate; Preferably, the monomercaptosilane compound is at least one selected from 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropylmethyldiethoxysilane.

5. The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to claim 1, characterized in that: The modified filler composition is prepared according to the following method: S21, dehydrating the electrolyte salt, the silane coupling agent and the optional polar solvent compound under vacuum stirring at 100 to 120° C. and a speed of 100 to 200 r / min for 1 to 5 hours to obtain a pretreated product; S22, reacting the pretreated product with the thermal conductive filler at 100-120° C. and a rotation speed of 100-200 r / min under vacuum stirring for 3-6 hours to obtain a modified filler composition.

6. The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to claim 5, characterized in that: The content of the thermal conductive filler in the modified filler composition is 70 to 85 parts by weight, the content of the electrolyte salt is 5 to 15 parts by weight, the content of the silane coupling agent is 2 to 7 parts by weight, and the content of the polar solvent compound is 0 to 15 parts by weight; Preferably, the thermally conductive filler is selected from at least one of aluminum oxide, magnesium oxide, zinc oxide, nickel oxide, aluminum nitride, silicon nitride, boron nitride and silicon carbide; Preferably, the electrolyte salt is an alkali metal salt and / or an ionic liquid; Preferably, the silane coupling agent is selected from 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl methyl diethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, At least one of ethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane; Preferably, the polar solvent compound is selected from at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, dimethoxymethane, 1,3-dimethoxypropane, 1,3-dioxolane, ethoxymethoxyethane, poly(ethylene glycol) dimethyl ether, poly(ethylene glycol) methyl ether methacrylate, poly(ethylene glycol) methyl ether, poly(ethylene glycol) methyl ether acrylate, poly(ethylene glycol) diglycidyl ether, poly(ethylene glycol) ethyl ether methacrylate, polyethylene glycol-bis(2-ethylhexanoate), poly(ethylene glycol) octyl ether, poly(ethylene glycol) phenyl ether acrylate, poly(ethylene glycol) tetrahydrofurfuryl ether, and poly(ethylene glycol) methyl ether toluene sulfonate.

7. The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to claim 1, characterized in that: The catalyst is selected from at least one of dibutyltin dilaurate, stannous octoate, zinc isooctanoate, bismuth isooctanoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether; preferably, the water absorbent is selected from at least one of molecular sieve desiccant, oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.

8. The method for preparing the electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to any one of claims 1 to 7, characterized in that: The method comprises uniformly mixing a siloxane-modified polyurethane prepolymer and a modified filler composition as well as an optional catalyst and a water absorbent to obtain an electrically detachable single-component siloxane-modified heat-conductive polyurethane hot melt adhesive.

9. The electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to any one of claims 1 to 7, characterized in that: The mixing step comprises: S31, dehydrating the polyol compound and the optional water absorbent at 100-120° C. and 100-200 r / min under vacuum stirring for 1-5 h, and then cooling to 70-90° C. to obtain a pretreated product; S32, adding a polyisocyanate compound and an optional catalyst to the pretreated product, stirring the mixture in a vacuum at 70 to 90° C. and at a speed of 100 to 200 r / min for 1 to 5 hours to obtain an isocyanate-diblocked polyurethane prepolymer; S33, reacting the isocyanate-dicapped polyurethane prepolymer with the monomercaptosilane compound under vacuum stirring at 70 to 90° C. and at a speed of 100 to 200 r / min for 1 to 5 hours to obtain a siloxane-modified polyurethane prepolymer; S34, reacting the siloxane-modified polyurethane prepolymer and the modified filler composition at 70-90° C. and at a rotation speed of 100-200 r / min with vacuum stirring for 0.5-2 h to obtain an electrically detachable single-component siloxane-modified thermally conductive polyurethane hot melt adhesive.

10. Use of the electrically detachable one-component siloxane-modified thermally conductive polyurethane hot melt adhesive according to any one of claims 1 to 7 in bonding electronic products.

Citation Information

Patent Citations

  • Electropeeling composition, adhesive using the same, and electropeeling multilayer adhesive

    CN101238191A

  • Detachable polyurethane hot melt adhesive, preparation raw materials and preparation method and bonding method of detachable polyurethane hot melt adhesive

    CN113897165A

  • Moisture-curable urethane composition

    JP2000234082A

  • Polymerization of a silane-modified polymer, which is produced by means of a radical chain polymerization, in a polyol or in a prepolymer with terminal isocyanate groups, and use thereof in polyurethane formulations

    US20240240069A1

  • Reactive polyurethane hot-melt adhesives having a low isocyanate monomer content

    WO2013171200A1

Cited By

  • High-filling low-viscosity single-component polyurethane hot melt adhesive and preparation method thereof

    CN121379492A